Learning Skills Using Simulated Teaching Materials by Students and Interns: Teachers’, Students’ and Interns’ Views (Bangladesh Journal of Medical Education, 2023)
This is a cross sectional study was conducted to find out views of teachers, students and interns on learning some common skills using simulated teaching materials by students and interns at undergraduate education in Bangladesh. The study was conducted from 1st January 2021 to 31st December 2021. One self-administered structured questionnaire was used to collect data from conveniently selected 100 medical teachers, 150 undergraduate students and 150 intern doctors by online Google format or in some cases face to face. It was found that out of five point Likert scales (ranging 1 to 5) the mean scores of the views of the respondents were more than 3.5 regarding the different common skills that should be learned by the students and interns using simulated materials before performing on real patient. It was also found that the teachers, students and interns statistically differ highly in their opinions regarding most of the issues. It can be concluded that some important skills can be learn by students and interns at the undergraduate medical course using simulated teaching materials before performing on real patient.Bangladesh Journal of Medical Education Vol.14(1) January 2023: 50-55